Formation of Dimers Composed of a Single Short dsDNA Connecting Two Gold Nanoparticles - Dachlika, Haya; Stern, Avigail; Rotem, Dvir; Porath, Danny (Journal of Self Assembly and Molecular Electronics, 2023)
We report synthesis of dimers composed of a single short double-stranded (ds)DNA molecule connecting two gold nanoparticles (GNPs). Such struc- tures may be useful for electrical transport measurements through dsDNA molecules and for other research purposes. When the DNA molecules are short with respect to the size of the GNP, gel electrophoresis cannot separ- ate GNPs with different numbers of DNA molecules attached to them. We present two methods to separate GNPs connected to single short thiolated single-stranded (ss)DNA. The separation is performed by hybridizing the DNA/GNP conjugates with long, partially complementary, ssDNA or with complementary ssDNA connected to GNPs of smaller size. The separated GNPs with a single short ssDNA were used to form dimers consisting of GNPs connected by a single short dsDNA molecule.